Development of Learning Media Using Ethnomathematics-Based Augmented Reality on Cube and Block Material - Ayu, Annisa; Nursyahidah, Farida; Prayito, Muhammad (Phenomenon : Jurnal Pendidikan MIPA, 2023)
The use of technology in Indonesian education is still quite far behind. Therefore, researchers conducted research aimed at developing android-based learning media using ethnomathematics-based Augmented Reality on cube and block material that is suitable for use and knowing student learning outcomes.  This type of research is Research and Development using the ADDIE development model which includes 5 steps, namely Analysis, Design, Development, Implementation, and Evaluation. Research instruments in the form of media validation questionnaires, material validation questionnaires, and learning outcomes tests. Media development using Blender 2.90.1 and Unity Engine 2018 4.36 software. Data analysis was carried out by normality, homogeneity, t-test, and learning due diligence. The results of this study can be concluded that (1) the percentage of validation of media experts is 91.5%, and material experts are 93%. (2) data from the field shows that the learning outcomes of students who obtain android-based learning media using ethnomathematics-based Augmented Reality are better than students who use lecture learning methods (conventional learning).